The Role Of Music Arts In Multicultural Education - awerman, Awerman; Ibnu Sina; Yurisman; Bambang Wijaksana; Yon Hendri (Kirana Publisher (KNPub), 2023)
Indonesia is a multicultural country, has a variety of regional cultures that spread from Sabang to Merauke, spread over thousands of islands with various cultures. This order has changed with globalization and the development of science, technology and art (IPTEKS). This has an impact on inequality and injustice in the world of education. Education in general is the provision of knowledge, experience and skills to students so that they can form positive behavior and can build noble character in an effort to shape national civilization by taking into account the values ​​of cultural diversity. Music arts education provides knowledge, experience, and competence through 5 basic components, namely: expression, appreciation, creation, harmony, and beauty which are integrated with multicultural education. This article describes the role of music in multicultural education which can raise awareness and concern in building a multicultural learning community in schools.